2023
DOI: 10.1093/infdis/jiad379
|View full text |Cite
|
Sign up to set email alerts
|

Multicountry Review of Streptococcus pneumoniae Serotype Distribution Among Adults With Community-Acquired Pneumonia

Lindsay R Grant,
Elizabeth Begier,
Christian Theilacker
et al.

Abstract: Background Nonbacteremic community-acquired pneumonia (CAP) is a leading presentation of severe pneumococcal disease in adults. Serotype-specific urinary antigen detection (UAD) assay can detect serotypes causing pneumococcal CAP, including nonbacteremic cases, and guide recommendations for use of higher valency pneumococcal conjugate vaccines (PCVs). Methods Adult CAP serotype distribution studies that used both Pfizer UADs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Pneumococcal pneumonia poses a significant challenge to global public health, especially in children and the elderly. Studies have shown that community-acquired pneumonia is the primary manifestation of severe pneumococcal disease in adults ( Grant et al, 2024 ), consistent with the findings of our study.…”
Section: Discussionsupporting
confidence: 93%
“…Pneumococcal pneumonia poses a significant challenge to global public health, especially in children and the elderly. Studies have shown that community-acquired pneumonia is the primary manifestation of severe pneumococcal disease in adults ( Grant et al, 2024 ), consistent with the findings of our study.…”
Section: Discussionsupporting
confidence: 93%
“… 1 , 5 , 34–36 A recent multi-country review found that serotypes covered by PCV13 still account for 34–54% of adult pneumococcal pneumonia cases after the introduction of PCV13 in children. 35 This indicates the continued presence of PCV13 serotypes as causative agents in adult pneumonia. Furthermore, a study across 33 high-income countries revealed that PCV13 serotypes comprised 30.6% of adult IPD cases in pediatric PCV13-using countries.…”
Section: The Latest Situation Regarding Serotype Replacement and Sero...mentioning
confidence: 98%
“…Additionally, PCV15 and PCV20 offer expanded serotype coverage compared to PCV13. 5 , 35 , 37 A multi-country review estimated the serotype coverage rates for PCV15 and PCV20 to be between 43–60% and 63–72% in the adult population, respectively, after the introduction of childhood PCV13. 35 In the study evaluating high-income countries, it was found that in addition to the serotypes included in PCV13, PCV15 and PCV20 potentially cover an extra 10.6% and 34.6% of serotypes, respectively, in pediatric PCV13-using countries.…”
Section: The Latest Situation Regarding Serotype Replacement and Sero...mentioning
confidence: 99%
See 1 more Smart Citation